1969
DOI: 10.1111/j.1469-8137.1969.tb06434.x
|View full text |Cite
|
Sign up to set email alerts
|

A Radiocarbon‐dated Pollen Diagram From North‐west Scotland

Abstract: SUMMARYA series of radiocarbon dates from critical levels in a pollen diagram from a site near Scourie, Sutherlandshire, proves the recorded events to be much younger than the trend of the pollen curves would suggest. Evidence of pine forest growing in the area during the late Atlantic and Sub-boreal confirms earlier observations that these forests persisted in north-west Scotland later than in many other parts of the British Isles. The extremely slow rate of accumulation between about 420 cm and 455 cm, 1320 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…The Timpendean site offers no views, and the nest would have been virtually in the dark. The presence of matai seeds in the deposit also suggests that this gully probably supported matai forest in the last few thousand years, similar to that which existed around Pyramid Valley a few kilometres to the southwest (Moar 1970). Therefore, the above comparison suggests to us that the Timpendean site was primarily accumulated by laughing owls.…”
Section: Falcon Site Timpendeansupporting
confidence: 58%
See 2 more Smart Citations
“…The Timpendean site offers no views, and the nest would have been virtually in the dark. The presence of matai seeds in the deposit also suggests that this gully probably supported matai forest in the last few thousand years, similar to that which existed around Pyramid Valley a few kilometres to the southwest (Moar 1970). Therefore, the above comparison suggests to us that the Timpendean site was primarily accumulated by laughing owls.…”
Section: Falcon Site Timpendeansupporting
confidence: 58%
“…Areas with heavier, deeper soils probably had forests dominated by matai, kahikatea and totara, but with numerous shrubby clearings of Coprosma, kanuka, manuka, and Muehlenbeckia vines (McGlone 1989). Moar's (1970) analysis of the pollen record at Pyramid Valley showed spikes of Phyilocladus, Hoheria and Gramineae at the base of the sequence about 5,000 years ago. The tailing off of these spikes correlates with the overall rise in tree and shrub pollen, largely due to the establishment of Nothofagus in the area at this time.…”
Section: History Of Vegetation Otiranmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CLB4 is suggested as beinp approximately equivalent to the Loch Lomond Stadial, it is likely that the Rumex/Oxyria maximum represents a period shortly after the coldest temperatures, and therefore contemporary with some of the transitional zones after the Artemisia maxima in other regions, such as the Cyperaceat-Rumex zone in eastern Skye (Walker et ai, 1988) or the Rumex zone at Yesnaby (Moar, 19696). The radiocarbon dates also support this idea.…”
Section: Llp-jcsupporting
confidence: 62%
“…At the conference was Professor Harry Godwin, Director of the Subdepartment of Quaternary Research, Cambridge, England, and an international leader in the application of pollen analysis to the history of vegetation, landscapes and climate. Harry Godwin suggested that Neville would benefit from a PhD in his department and, in 1961, with DSIR support, Neville began a PhD at Cambridge on the late-glacial and post-glacial vegetation history of south-west Scotland, Shetland and Orkney Islands with Richard West as his supervisor (Moar 1969b(Moar , 1969c(Moar , 1969d. The Subdepartment of Quaternary Research was in the forefront of Quaternary studies at that time and Neville had as colleagues leading Quaternary scientists such as Donald Walker and Nicholas Shackleton, and travelled widely in Europe to attend conferences.…”
mentioning
confidence: 99%